Health literacy issues in the health inequality context - Mirczak, Anna (Journal of Education, Health and Sport, 2017)
Introduction. Health literacy is defined as the ability to read, understand and act on health information to make appropriate health decisions. Many factors can contribute to an individual’s health literacy as age, sex, level of education, housing, occupation, income, individual’s amount of experience in the health care system and cultural factors determining attitudes and health beliefs. Objective. The aim of this publication was to draw attention to the importance of low levels of health literacy in the development of health inequalities. Description of the state of knowledge. According to the literature, people with inadequate or marginal health literacy skills have higher risk of premature death and hospitalization due to many health problems, and also have less access to health care mainly through communication problems with medical staff than general population. Summing up. Nowadays the process of building health literacy of citizens is becoming an important challenge for public health, because it promotes equal opportunities in health, minimizes the costs associated with the treatment process, increases of ability to effectively self-care management (especially in chronic diseases), and thus improves the health of the general population.